Reconciliation of the Washington Consensus with the Beijing Model in Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
In this study, we argue that an approach which will reconcile the two opposing camps in Sino-African relations and bring the most progress is a “middle passage” that greases contradictions and offers an accommodative, balanced and pragmatic vision on which Africans can unite. We present a case under which countries can substantially enhance the prospect of development if an African consensus builds on a merger between the Western and Chinese models. We balance national interest with human rights, sovereign authority with individual rights and economic goals with political rights. The chapter presents arguments on the need for a development paradigm in Africa that reconciles the Washington Consensus with the Beijing Model. The analytical framework is organised in three main strands, notably: (i) historical perspectives and contemporary views; (ii) reconciliation of dominant schools of thought and paradigms surrounding Sino-African relations and (iii) practical and contemporary implications. Reconciled schools of thought are engaged in four main categories: optimists versus (vs.) pessimists; preferences in rights (human vs. national, idiosyncratic vs. sovereign and political vs. economic) and the Beijing model vs. the Washington Consensus.
Keywords: F19; F21; O10; O19; O55; 330; Economic relations; China; Africa